Investigation of compositional analysis and physical properties for Ni-Cr-Nb alloys using laser-induced breakdown spectroscopy - Salloom, Hussein; Hamad, Tagreed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
In this work, laser-induced breakdown spectroscopy (LIBS) analysis is optimized for direct estimation of elemental composition, thermal conductivity and hardness for Ni-Cr-Nb alloys. These alloys were chosen with a variable elemental content of niobium and chromium. The influence of laser energy and shot numbers on measuring line intensity was investigated. Based on the ratio between two spectral lines, calibration curves were formed to estimate the element concentration and LIBS results were confirmed with related energy-dispersive X-ray spectroscopy (EDS) data. Hardness and thermal conductivity estimation using LIBS were done by measuring the ratio between two spectral lines, plasma excitation temperature and electron density for different samples. Semi-empirical formulas correlated hardness and thermal conductivity with plasma temperature were established.
Optica Applicata, Vol. 51, 2021, nr 3, s. 429-444
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; LIBS technique; elemental analysis; nickel alloys; hardness